Pengaruh Akun Tiktok Pandawara Group Terhadap Kampanye Pengurangan Sampah Plastik Pada Generasi Z - Putra, Kevin Naufal; Raymond, Andree (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Pandawara Group is a non-governmental organization that campaigns for the plastic waste reduction movement through Tiktok social media. The purpose of this study is to determine the effect of Pandawara Group's Tiktok account on the Plastic Waste Reduction Campaign in generation Z. In this case, Pandawara Group held a positive movement that has the aim of reducing plastic waste. In this case, Pandawara Group held a positive movement that aims to reduce plastic waste. However, the volume of plastic waste and the disaster caused by the large amount of plastic waste scattered around is still quite a lot. Therefore, the Pandawara Group Tiktok Account, which was built by five young people, carried out a positive movement to change people's behavior regarding plastic waste which can endanger the surrounding environment. This study uses Quantitative research methods with descriptive research types. With a population of 7.7 million people, a sample of 100 people was obtained using the slovin formula. The technique used for this research is Purposive Sampling where this technique is used in accordance with judgment or judgmental of who is qualified to be a respondent from the entire population. Research results obtained from the R value there is a strong relationship. The results of the coefficient of determination (R square) value that the Tiktok Pandawara Group Account on the Campaign has a high or strong influence. While the rest, which is only a small part, is influenced by other variables.